Building Marketing Expansion of Mekarbuana Tourism Products Through a Push and Pull Strategy - Sumarni, Neni; Nurlenawati , Netti (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
This research aims to determine Mekarbuana's tourism marketing strategy by using a push-and-pull strategy to build its marketing expansion. The results of this research show that there is an increase in the market obtained by Mekarbuana tourism when implementing the push and pull strategy, but it is not too big, this is because the implementation has only been running for two months during its implementation period. The research was conducted using a qualitative single case study method: collecting, presenting, analyzing, triangulating and testing validity and making conclusions and suggestions. The push and pull strategy can be applied in marketing Mekarbuana tourism products and can expand its marketing if Mekarbuana tourism can consistently implement this strategy.